TANGGUNG JAWAB NOTARIS SETELAH BERAKHIR MASA JABATANNYA DITINJAU DARI UNDANG-UNDANG NO. 30 TAHUN 2004 JO UNDANG-UNDANG NO. 2 TAHUN 2014 TENTANG JABATAN NOTARIS - IRWANDA IRWANDA (PREMISE LAW JURNAL, 2016)
A notary is a public official appointed by the Government; in this case, the Minister of Justice and Human Rights of Republic of Indonesia, who has a function to provide a service to the society and an authority to make an authentic deed in almost all legal actions as referred to the laws. This is a normative judicial research with prescriptive analysis which approaches the research problems by reviewing the prevailing legal provisions in the Notarial Law stipulated in UUJNNo. 30/2004 (the Law on Position of Notary) juncto UUJNNo. 2/2014. The results show that he has to make an authentic deed in line with the prevailing legal provisions in the Notarial Law as stipulated in the UUJN No. 30/2004 juncto the UUJNNo. 2/2014 and Article 1868 of Civil Code regarding the Procedure of the Making of Authentic Deed for Public Official. Notary whose tenure has ended is still responsible for the deeds he has made until he passes away because there is no regulation in the prevailing provisions that obviously states the time limit of the responsibility of a Notary for the deed he has made. He is also responsible for the making of the authentic deed concerning the names of the persons appearing and the accuracy of the date of the deed. In case there is any suit to the authentic deed.   Keywords:       Notary’s Responsibility, Tenure Ends, UUJN No. 30/2004 juncto UUJN No. 2/2014